Hubungan Kepatuhan Minum Obat Antihipertensi Terhadap Tercapainya Target Terapi Pasien Hipertensi di Puskesmas Wirobrajan Yogyakarta - Fani Mardina Cahyani (Universitas PGRI Madiun, 2018)
Center for Health Data and Information (Pusdatin) Province of Yogyakarta (DIY) 2016 based on Riskesdas 2013, DIY province with hypertension prevalence 12,8% rank 3 in Indonesia after North Sulawesi and South Kalimantan. The case data of family visits, hypertension disease has become the second most dominant disease for family groups in DIY. The top ten diseases diagnosed in outpatients in Puskesmas according to the report of integrated surveillance system, hypertension became the third order after diarrhea and influenza case. The purpose of this study was to determine the relation of adherence to antihypertensive medication to the achievement of hypertension therapy target at Wirobrajan Health Center Yogyakarta. This research is a type of observational research with cross sectional method. Method of sampling with total population with inclusion criteria that visit to Wirobrajan Health Center. The sample in this study were 50 patients. Primary data collection was conducted using MMAS questionnaire. The result of chi-square test between adherence level and the achievement of therapeutic target that is p value 0,005 <0,05 this indicates the relation between adherence level with the achievement of therapy target.Keywords: adherence, hypertension, therapeutic target